RinA controls phage-mediated packaging and transfer of virulence genes in Gram-positive bacteria - Ferrer, Maria D.; Quiles-Puchalt, Nuria; Harwich, Michael D.; Tormo-Mas, María A.; Campoy, Susana; Barbe, Jordi; Lasa, Inigo; Novick, Richard P.; Christie, Gail E.; Penadés, José R. (2017)
Phage-mediated transfer of microbial genetic elements plays a crucial role in bacterial life style and evolution. In this study, we identify the RinA family of phage-encoded proteins as activators required for transcription of the late operon in a large group of temperate staphylococcal phages. RinA binds to a tightly regulated promoter region, situated upstream of the terS gene, that controls expression of the morphogenetic and lysis modules of the phage, activating their transcription. As expected, rinA deletion eliminated formation of functional phage particles and significantly decreased the transfer of phage and pathogenicity island encoded virulence factors. A genetic analysis of the late promoter region showed that a fragment of 272 bp contains both the promoter and the region necessary for activation by RinA. In addition, we demonstrated that RinA is the only phage-encoded protein required for the activation of this promoter region. This region was shown to be divergent among different phages. Consequently, phages with divergent promoter regions carried allelic variants of the RinA protein, which specifically recognize its own promoter sequence. Finally, most Gram-postive bacteria carry bacteriophages encoding RinA homologue proteins. Characterization of several of these proteins demonstrated that control by RinA of the phage-mediated packaging and transfer of virulence factor is a conserved mechanism regulating horizontal gene transfer.